A newly developed renewable energy driven multigeneration system with hot silica sand storage for power, hydrogen, freshwater and cooling production - Yapicioglu, Arda; Dincer, Ibrahim (ELSEVIER, 2023)
In this study, a renewable energy-driven multigenerational system is designed to produce useful outputs, such as electricity, cooling, freshwater, and hydrogen by applying energy, and exergy methodologies to evaluate its performance. The multigenerational system aims to make use of solar and wind energy in combination with electric heating to heat up the sand particles and gravity-fed them through a pressurized fluidized bed heat exchanger heating and pressurizing the air and producing electricity by spinning the gas generator. The leftover steam is used for absorption cooling and freshwater production through desalination which is partially used to produce hydrogen. The produced energy can be stored in the form of sand and used whenever necessary for the community. Another important aspect to consider is the system economics, which makes silica sand a potential storage option as its stable and inexpensive at 35-45$/ton. The multigenerational system uses renewable energy sources and stores energy with the use of a thermal energy storage material and reduces the environmental impact by emitting much less carbon emissions compared to other power generation and storage methods. The overall energy and exergy efficiencies of the multigenerational system are found as 53.3% and 49.8%, respectively.
Keywords: Solar energy; Renewable energy; Thermal energy storage; Sustainable energy; Efficiency; Exergy; INTEGRATED-SYSTEM; SOLAR; DESALINATION; Science & Technology - Other Topics; Energy & Fuels